Estimate of the travelling wave speed for an integro-differential equation. (February 2019) - Bessonov, N.; Beuter, A.; Trofimchuk, S.; Volpert, V.
Abstract: Travelling waves for nonlocal reaction–diffusion equations are studied. The minimax representation of the wave speed is obtained. It is used to obtain analytical estimates and asymptotic values of the speed. Two regimes of wave propagation are identified. One of them is dominated by diffusion and another one by the nonlocal interaction.